Public spheres, private lives in modern Japan, 1600-1950: essays in honor of Albert M. Craig - Bernstein, Gail Lee; Gordon, Andrew; Nakai, Kate Wildmann (Harvard East Asian monographs, 2005)
Preliminary Material /Gail Lee Bernstein , Andrew Gordon and Kate Wildman Nakai --Gail Lee Bernstein, Andrew Gordon, and Kate Wildman Nakai /Gail Lee Bernstein , Andrew Gordon and Kate Wildman Nakai --Conventional Knowledge in Early Modern Japan /Mary Elizabeth Berry --Local Autonomy in Early Meiji Japan: Competing Conceptions /Kyu Hyun Kim --Tanaka Shōzō’s Vision of an Alternative Constitutional Modernity for Japan /Timothy S. George --A Land of Milk and Honey: Rural Revitalization in the 1930s /Kerry Smith --Chisui: Creating a Sacred Domain in Early Modern and Modern Japan /Patricia Sippel --Taming the Iron Horse: Western Locomotive Makers and Technology Transfer in Japan, 1870–1914 /Steven J. Ericson --Women’s Rights and the Japanese State, 1880–1925 /Barbara Molony --Men’s Place in the Women’s Kingdom: New Middle-Class Fatherhood in Taishō Japan /Harald Fuess --Social Networks Among the Daughters of a Japanese Family /Gail Lee Bernstein --Rethinking Japanese-Chinese Cultural Relations in the 1930s /See Heng Teow --Mocking Misery: Grass-Roots Satire in Defeated Japan /John W. Dower --Index /Gail Lee Bernstein , Andrew Gordon and Kate Wildman Nakai --Harvard East Asian Monographs /Gail Lee Bernstein , Andrew Gordon and Kate Wildman Nakai.